Exhumation and structural evolution of the high-elevation Malcante Range, Eastern Cordillera, NW Argentina. (January 2021) - Payrola, Patricio; Zapata, Sebastian; Sobel, Edward R.; Papa, Cecilia del; Pingel, Heiko; Glodny, Johannes; Ledesma, Jonathan
Abstract: As an integral part of the Eastern Cordillera, the fault-bounded Malcante mountain range (up to 5100 m) in the NW Argentine Andes (ca. 25°S) is located in the transition between the arid Puna Plateau to the west and the humid broken foreland to the east. At this latitude, the topographic gradient of the eastern Andean margin forms an efficient orographic barrier that causes pronounced east–west rainfall and surface-process gradients. In this setting, the Malcante Range is an important, yet poorly studied structural high formed during the Cenozoic topographic growth of the Central Andes. In this study, we combine (a) detailed field observations, (b) a two-dimensional structural reconstruction, (c) apatite fission track and (U–Th-Sm)/He thermochronology of bedrock samples from a vertical transect across the western flank of the Malcante Range, and (d) inverse thermal modelling using QTQt software with the aim of deciphering the exhumation history of this mountain range. Field data indicate the presence of an angular unconformity between Cenozoic foreland deposits and older sedimentary strata, suggesting an initial episode of deformation during the middle-late Eocene, while our thermal model constrains the onset of exhumation at 10 Ma. We suggest that exhumation was related to the unroofing of the easily erodible sedimentary cover, which prevented significant initial surface uplift. This may have changed as more resilient bedrock was exposed at 5 Ma according to the thermal model, promoting rapid rock uplift. In combination with published data, our thermochronology allows us to speculate on the existence of a zone of deformation concentrated in the area of the present-day Pasha (24.5°S), Malcante (25°S), and Agua de Castilla (25.4°S) mountain ranges by ca. 10 Ma. Highlights: Calchaquí high-mountains with anomalous position. Angular unconformity in the contact between Paleogene post-rift deposits and middle Eocene foreland deposits. Malcante Range exhumation start at 10 Ma. Accelerated uplifting during the Pliocene.